Adoption of modern beekeeping and its impact on honey production in the former Mwingi District of Kenya: assessment using theory-based impact evaluation approach. (25th June 2015) - Affognon, Hippolyte D.; Kingori, W.S.; Omondi, A.I.; Diiro, M.G.; Muriithi, B.W.; Makau, S.; Raina, S.K.
Abstract : This study used the theory-based impact evaluation approach to understand as to how promotion of beekeeping by the Commercial Insects Programme (CIP) of the International Centre of Insect Physiology and Ecology ( icipe ) has had an impact on honey production in the former Mwingi District of Kenya (now merged into Kitui County). We examined the adoption of modern hives promoted by icipe and applied data envelopment analysis (DEA) to assess the technical efficiency (TE) of participants in CIP. CIP participants had an average TE of 0.56, which was significantly higher than that of non-participants in the former Kitui District (average TE of 0.26). Those who adopted modern hives achieved the highest average levels of TE (0.59). The study fits a Probit model to identify the drivers of adoption and a Tobit model to assess the intensity of adoption of modern hives. The propensity score matching approach was used to evaluate the impact of modern hives on honey production. Results indicate that perceptions about the yield and quality of honey obtained from modern hives significantly increased beekeepers' adoption decisions. The intensity of adoption expressed as the proportion of modern hives owned by beekeepers was significantly high among farmers who participated in CIP. A positive and significant relationship was observed between the adoption of modern hives and the quantity of honey produced. The present study indicates, through the average TE, that considerable room still exists for the improvement of beekeeping and provides strong evidence for scaling up the dissemination of modern hives in areas of Kenya with high potential.